Structuration theory: open the black box of integrated care - Esslinger, Adelheid Susanne (Igitur, Utrecht Publishing & Archiving, 2009)
INTRODUCTION: The health care system is in transition. Integrated cares solutions are prominent and even forced by health care policy. But how can we understand the needs of different stakeholders in this system? Why do they still not act effectively and efficiently together? A closer look, using the structuration theory of Anthony Giddens, may be helpful. THEORY: The theory of structuration enables people to explain social interactions. As this is a matter of fact, the health care system was analyzed by the author in her habilitation thesis. The focus of the study laid on the effective and efficient care of the very old people in Germany. The structuration theory was presented, and as an example of practical translation of the theory, the implementation of the ‘Pflegestützpunkte’ (service point for care) was described. PRACTICE: Giddens' structuration theory is on the one hand complex in theory, and simple on the other hand in practice. Choosing the paradigm may be helpful to explain the motivation of the different stakeholders in the health care system. It would be necessary to create a suitable questionnaire, to get deeper insight in how the different actors in the system act and react. Such a questionnaire should be based on Giddens' theory. The following three dimensions are needed: structure (including domination, legitimation, and signification), interaction (including power, sanctioning, and communication) and modality/duality (including instruments of power, norms and interpretation).